Sharp Foreign Body within the Thorax Concurrent with Pneumomediastinum in an Adult Cow: A Case Report - Abdelhakiem, Mohammed Ahmed Hamdy (Journal of Advanced Veterinary Research, 2018)
According to the author knowledge, this report described for the first time pneumomediastinum that was concurrent with sharp foreign body syndrome in an adult recently parturient cow, which was admitted with signs of traumatic reticuloperitonitis. The radiographic examination revealed both sharp metallic foreign body (nail) within the thoracic cavity and pneumomediastinum. The latter is recognized by visualization of the structures, which could not be seen on the radiograph of normal animals. The animal did not receive any type of treatment and its owner was advised with its slaughter.